ARTIFICIAL INTELLIGENCE (AI) DALAM PENGEMBANGAN NANOPARTIKEL SEBAGAI SISTEM PENGHANTARAN OBAT - Hannie Fitriani; Muhammad Hidayatullah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Nanotechnology has developed rapidly in various aspects, one of which is in the pharmaceutical industry, particularly in drug delivery systems. The Nanotechnology as a drug carrier can increase the efficiency of delivery systems. The process of developing drug formulations using nanoparticles remains highly complex, expensive, and time-consuming. The application of Artificial Intelligence (AI) is a rapid method and is expected to improve drug delivery through nanotechnology effectively, efficiently, and accurately, starting with pre-formulation and formulation. This article aims to discuss the application of various AI methods such as Machine Learning (ML), Deep Learning (DL), and Neural Networks (NN) in the development of nanoparticle-based drug delivery systems. This research was conducted through a review of the latest literature from the last three years (2022–2024) accessed from various scientific databases such as PubMed, ScienceDirect, and Google Scholar. The AI in the development of nanoparticles as drug delivery systems has significant potential to increase efficiency, accelerate the development process, and reduce research costs and time. However, AI implementation requires multidisciplinary collaboration and improved data quality for model validation.